(untitled) (Journal of Geography and Environmental Management, 2026)
This article examines the comprehensive monitoring of land suitability for agriculture. The primary objective of the study is to assess the current state of land resources and determine their potential for efficient and environmentally sound agricultural use. Comprehensive land suitability monitoring is a scientific and practical process aimed at a comprehensive assessment of the quality, productivity, and environmental status of land resources. This monitoring includes the study of the physicochemical properties of soil, climate conditions, water resources, topography, and vegetation. The analysis takes into account soil fertility, agro-ecological conditions, climatic factors, the degree of land degradation, and anthropogenic impact. The primary goal is to identify opportunities for efficient land use and sustainable agricultural development. This article presents the results of a comprehensive (space, geodetic, and radioecological) survey of the Semipalatinsk Region, conducted to permit the agricultural use of land plots formerly used as nuclear test sites. The results of geodetic monitoring conducted at the Balapan and Telkem test sites were processed in a geographic information system (GIS), and cartographic products were generated. This revealed surface deformations, temperature anomalies, and levels of radioactive contamination, and produced environmental assessment maps. The results formed the basis for the assessment and development of proposals for the use of land plots affected by nuclear tests that were deemed radiation-safe. The study’s results allow for specific recommendations to improve soil fertility, prevent erosion and desertification, and mitigate environmental risks. Furthermore, this process promotes rational land management, appropriate crop placement, and the conservation of natural resources. Comprehensive monitoring is an essential tool for maintaining long-term soil productivity.